Optimal Decision-Making in Chinese Cross-Border Mergers and Acquisitions: A Perspective of Overbidding - Yanping Bao; Chan Lyu; Xia Wu; Jun Lian (Complexity)
Chinese domestic firms engage actively in the cross-border merger and acquisition (CBMA) markets, which are crucial in China’s foreign investment economics. Acquisition premium has attracted stakeholders’ attention to determine whether the CBMA decision is optimal. This study employs a novel model to assess decision-making efficiency by overbidding based on a profit maximization assumption. Based on the Chinese CBMA transaction data from 2009 to 2019 of Chinese acquiring firms, the descriptive analysis indicates the widespread overbidding phenomenon in Chinese CBMAs. Moreover, empirical findings reveal that SOEs (vs. non-SOEs) experience less overbidding among acquiring firms. This study also shows that firms from the high-tech industry tend to be less overbidding (more efficient) in the CBMAs’ setting. The findings may have policy implications for China’s outward investment efficiency.